Testing of the equipment on the modern era shipwreck at Otočac (In situ, 2024)
The project Application and potential of non-destructive methods of archaeological research on the example of the post-medieval shipwreck at Otočac on the island of Korčula was motivated by the idea of collecting data by measuring electrical potential, pH value and multispectral imaging. The project was launched with the aim of testing non-destructive, affordable and user-friendly remote sensing methods for the analysis of archaeological sites.
Keywords: Modern era; Otočac; shipwreck; korčula